The Training Needs of In-Service Teachers for the Teaching of Historical Thinking Skills in Compulsory Secondary Education and the Baccalaureate Level - Guerrero-Romera, Catalina; Perez-Ortiz, Antonio Luis (Frontiers in Education, 2022)
In a context of change such as that which is currently taking place in the field of social sciences education, the ongoing training of in-service teachers is a key element as only by bringing about a true change in their teaching practice can teaching approaches and the processes of history education be improved. The present paper aims to contrast a theoretical model with a questionnaire designed to identify the training needs of secondary and baccalaureate teachers with regard to the teaching of the historical thinking skills. A quantitative research methodology has been employed with a non-experimental design in which an exploratory and confirmatory factor analysis and a hierarchical clustering analysis have been carried out. After carrying out and applying the analysis, a questionnaire (NFPA) was elaborated, the construct validity and reliability of which were satisfactory and appropriate. The results will make it possible to detect and identify needs and deficiencies in ongoing teacher training. Furthermore, it will become possible to discover new elements in order to improve training processes from the point of view of in-service teachers